Clinical experience of ingenol mebutate gel for the treatment of Bowen's disease. Issue 4 (31st January 2018) - Lee, Dong Won; Ahn, Hyo Hyun; Kye, Young Chul; Seo, Soo Hong
Abstract: There are only a few anecdotal case reports about Bowen's disease (BD) treated with ingenol mebutate (IM) gel but no clinical study has been published yet. The aim of this study was to evaluate the effectiveness of IM gel in the treatment of BD and to observe the therapeutic efficacy of IM alone or IM with ablative fractional laser pretreatment. Nineteen patients with BD or squamous cell carcinoma in situ confirmed by skin biopsy were enrolled. IM was applied with 0.015% gel on facial lesions for 3 days consecutively and 0.05% gel on other sites for 2 days consecutively, with a 5‐mm application margin around the visible lesion. Nine patients applied IM gel immediately following fractional CO2 laser treatment. Two patients were lost to follow up and a total of 17 patients were enrolled. Nine patients (9/17, 52.9%) had a clinically complete response at 2 months after treatment. Among the patients treated with the fractional CO2 laser before applying IM gel, eight (8/9, 88.9%) showed a complete response and one (1/9, 11.1%) showed partial response. Among the patients treated with IM gel alone, only one patient (1/8, 12.5%) showed a complete response, four (4/8, 50%) showed a partial response and three (3/8, 37.5%) did not respond to therapy. IM gel alone seems to have limited value for treatment of BD; however, a combination therapy with the ablative fractional laser can increase its therapeutic effectiveness.